Broadening horizons: 25 years of advancing cognitive development research through linguistic and cultural diversity - Rochanavibhata, Sirada; Atagi, Natsuki (Frontiers in Developmental Psychology, 2025)
Over the past 25 years, research in cognitive development has begun to embrace linguistic and cultural diversity. For example, the field has begun to move away from focusing on predominantly WEIRD, English-speaking populations, and rather, moved toward including historically underrepresented groups. The field has also transitioned from deficit perspectives of linguistic and cultural diversity to embrace an asset-based model in which differences from the “norm” in cognitive development are viewed as strengths. Additionally, more continuous representations of linguistic and cultural diversity often complement the more traditional, binary conceptualizations of linguistic (e.g., monolingual vs. bilingual) and cultural (e.g., Eastern vs. Western) backgrounds. Through these more representative accounts of our heterogeneous society, we have gained valuable insights into the development of cognitive processes in children. This mini review will summarize recent research findings in sub-disciplines of cognitive development, including attention, perception, executive function, and language, that were made possible by including linguistically and culturally diverse populations. We also identify future challenges related to systematic measurement and assessment of multilingualism and culture. We conclude by discussing the way forward, including large-scale collaborative efforts in developmental research (e.g., ManyBabies, Wordbank).